Ethnic Identity and Labor-Market Outcomes of Immigrants in Europe - Alberto Bisin; Eleonora Patacchini; Thierry Verdier; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
We study the relationship between ethnic identity and labor-market outcomes of non-EU immigrants in Europe. Using the European Social Survey, we find that there is a penalty to be paid for immigrants with a strong identity. Being a first generation immigrant leads to a penalty of about 17 percent while second-generation immigrants have a probability of being employed that is not statistically different from that of natives. However, when they have a strong identity, second-generation immigrants have a lower chance of finding a job than natives. Our analysis also reveals that the relationship between ethnic identity and employment prospects may depend on the type of integration and labor-market policies implemented in the country where the immigrant lives. More flexible labor markets help immigrants to access the labor market but do not protect those who have a strong ethnic identity.
Keywords: 330